Changes in serum immunomolecules during antibiotic therapy for Mycobacterium avium complex lung disease. (April 2014) - Kim, S.‐Y.; Koh, W.‐J.; Park, H. Y.; Jeon, K.; Kwon, O. J.; Cho, S.‐N.; Shin, S. J.
Summary Little information is available regarding changes in immune status for patients with Mycobacterium avium complex (MAC) lung disease during antibiotic therapy. Serum immunomolecules from 42 patients with MAC lung disease were assayed comparatively using an array‐based system according to (i) patients with MAC lung disease at the time of diagnosis versus healthy controls and (ii) alterations after 12 months of antibiotic therapy in the MAC lung disease group. In addition, cytokine analyses were performed to determine whether cytokine responses were associated specifically with the disease phenotype, treatment outcome and aetiological agent. Notably, the serum concentrations of type 1 cytokine‐associated molecules, such as CD40L, interferon (IFN)‐γ, interleukin (IL)‐8 and IL‐23, were decreased significantly in patients at the time of diagnosis, suggesting that these molecules may serve as indicators of host susceptibility to MAC disease. Although the overall serum level of T helper type 1 (Th1)‐related molecules, such as CD40L and IFN‐γ, was restored after treatment, Th17‐related cytokines, such as IL‐17 and IL‐23, were down‐regulated significantly at 12 months post‐treatment compared to pretreatment. Furthermore, these cytokine patterns differed among patient subgroups. Decreased serum concentrations of IL‐17 and/or IL‐23 were associated with failure of sputum conversion, the fibrocavitary disease phenotype and M. intracellulare lung disease. Thus, the reciprocal balance between Th1 and Th17 immunity during antibiotic therapy for MAC lung disease is critical for dictating the treatment response. In conclusion, a low level of Th1‐related immunomolecules may perpetuate MAC lung disease, and the serum concentrations of Th17‐related cytokines can reflect the treatment outcome, disease phenotype and aetiological agent.